Pengaruh Pola Makan terhadap Kejadian Karies Gigi Anak - Akmal Alif Muzakki; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Dental caries is a dental tissue disease characterized by tissue damage, starting from the surface of the tooth (grooves, fissures, and interproximal areas) extending towards (Braurer). Cariogenic foods are foods that can cause dental caries. The nature of cariogenic foods is that they contain lots of carbohydrates, are sticky and break down easily in the mouth. The purpose of this article is to determine the effect of food type, food frequency, and amount of food on the incidence of dental caries. The research method used was a literature review of various current scientific literature, including journals, textbooks and research articles. According to the results of research conducted by Febrian, et al., (2015), it shows that there is a significant relationship between types of cariogenic snacks and the incidence of caries. There is an influence of food frequency on the occurrence of dental caries in children. The amount of food consumed by a person or group of people at a certain time can trigger bacteria in the oral cavity to produce acid, causing the pH of saliva to decrease and demineralization to occur which will last for 30 to 40 minutes after eating.